Avaliação in vitro e in vivo dos efeitos da intoxicação aguda com o inseticida organofosforado, clorpirifós, e da eficácia do tratamento farmacológico empregado na intoxicação sobre a modulação cardiorrespiratória tônica e reflexa - Felippe, Igor Simões Assunção (2017)
In Brazil, the usage of agrochemicals has grown significantly in recent years, making the country one of the world leaders in consumption. Organophosphates (OFs) have been associated with cardiovascular diseases and intoxication induced by these compounds has a high mortality rate. Previous studies from our laboratory have shown that acute exposure to an OP compound, chlorpyrifos (CPF), in rats impairs the cardiovascular responses of the baroreflex and chemoreflex. However, it was not possible to address in this study the effects induced by the exposure to this compound on the respiratory function, despite the important modulation that the cardiovascular reflexes, particularly the chemoreflex, exert on respiratory parameters. Considering that the cardiorespiratory function plays a major role in the survival of intoxicated individuals, it seems of pivotal importance the development of detailed studies, using in vitro and in vivo approaches, to investigate the effects of CPF exposure on the tonic and reflex cardiorespiratory modulation. Additionally, the present controversy surrounding the standard treatment adopted in OP intoxication and the absence of studies focusing on antidote treatment and restoration of OPinduced cardiovascular damage, further reinforces the importance of studies in the field. In the present study, in vitro and in vivo protocols were used to evaluate the effects of acute intoxication with CPF on tonic and reflex cardiorespiratory activity and to evaluate whether the pharmacological treatment with the antidotes atropine (ATR) and pralidoxime (2-PAM) was capable of reversing the damage on the chemoreflex function previously observed. Two groups (CPF and control) were submitted to the in vitro protocol involving the working heart-brain stem preparation (WHBP). In this preparation, basal activities of the phrenic (PNA), recurrent laryngeal (RLN) and thoracic sympathetic (tSNA) nerves, in addition to heart rate and perfusion pressure were recorded. Associated with these recordings, in situ activation of the chemoreflex and baroreflex was also performed, followed by procedures of bilateral vagotomy and blockade with atenolol and hexamethonium. In the in vivo model, animals were grouped according to different combinations of treatments with CPF, ATR and 2-PAM. Twenty-four hours after treatment, activation and records of the chemoreflex function were performed. The presence of intoxication signs, ataxia, tremor and sialorrhea, was evaluated along three hours after receiving injections of CPF or saline; and after the treatment with ATR and/or 2-PAM. For both in vitro and in vivo models, the activities of plasma butyrylcholinesterase (BuChE) and cerebral acetylcholinesterase (AChE) in the brainstem were quantified. Additionally, in the in vivo protocol, punchs of brain stem sections containing the nucleus ambiguous, rostral ventrolateral medulla (RVLM), the pre-Bötzinger complex (preBöTC) and the nucleus of the solitary tract (NTS) were collected for individualized quantification of cerebral AChE activity. Our data showed that acute exposure to CPF led to impairment of the chemoreflex responses either in the in vitro or in vivo models. Additionally in the in vitro study, an impairment of baroreflex function was also observed, indicated by the reduced reflex-induced inhibition of the sympathetic activity in poisoned animals. Concerning the respiratory function in the WHBP, a reduction in the amplitude of PNA and of the RLN post-inspiratory discharge was also observed in intoxicated animals when compared to the control group. CPF poisoned animals also presented a higher tachycardia following vagal section when compared to control group. Blockade with hexamethonium induced an increase in perfusion pressure of CPF intoxicated animals. In the in vivo model, treatment with the antidotes, ATR and 2-PAM, induced differentiated effects on chemoreflex responses in intoxicated animals. Treatment with 2-PAM restored the impairment of the chemoreflex-induced hypertension observed in CPF intoxicated animals. On the other hand, treatment with atropine attenuated the impairment of the bradycardic response of the chemoreflex observed in poisoned animals. Both treatments seemed to exert a protective effect on the tachypneic response of the chemoreflex. All CPF intoxicated animals showed a marked inhibition of the plasma butyrylcholinesterase and acetylcholinesterase activities either in the brainstem or in the isolated punchs. CPF animals also exhibited signs of acute intoxication, which were attenuated or abolished by the antidote treatments. Our data indicate that CPF intoxication induces an impairment of the chemo and baroreflex responses and that the antidote treatment seems to partially restore the damage observed in the cardiorespiratory function.